Pó de rocha como fonte de nutrientes no contexto da agroecologia - Brandão, Juliana Andréia Vrba (2012)
The aim of the search was evaluate alternatives to accelerate the solubilization of minerals contained in rock powder. In the first experiment, presented in Chapter 2, the objective was to evaluate the effect of the fungus Aspergillus niger strain CCT4355 and vinasse in the solubilization of minerals contained in the basalt powder. The experiment in vitro consisted in the treatments: vinasse + A. niger (VF), rock powder + vinasse (PV) and rock powder + vinasse + A. niger (PVF). The basalt powder used had grains smaller than 0.053 mm. In PV the solubilization of calcium, magnesium, potassium, zinc and copper was greater than PVF, demonstrating the potential of vinasse as solubilizing agent. It concludes that mixtures of vinasse and rock powder have significant potential for production of low cost biofertilizer. In the second experiment, presented in chapter 3, the objective was to evaluate the effect of A. niger in the release of nutrients from the powder of basalt and phonolite in vitro dissolution tests. The treatments were: powder of phonolite + medium (FM), powder of phonolite + medium + fungus (FMA), powder of basalt + medium (DM), powder of basalt + medium + fungus (DMA) and fungus + medium (MA). It was observed that A. niger was able to produce organic acids which solubilized the rock powders and interacted in different ways with the nutrients. It is concluded that the strain CCT4355 of A. niger has potential as a solubilizing agent of silicate rock powder. The chapter 4 presents the results obtained with mixtures of vermicompost and basalt powder, and the two objectives were: i) determine the availability of nutrients in bioproduct resulted of vermicompost, prepared with viii the addition of powder of basalt, and ii) evaluate the effect of rock powder, with and without vermicomposting, in short cycle culture, using Italian zucchini (Cucurbita pepo) as a indicator plant. The application of basalt powder in the vermicompost layers provided the pH raising of the product obtained at the end of 55 incubation days, but the vermicomposting was not able to provide nutrients presents in the basalt powder. The application of vermicompost, with and without addition of rock powder, had an effect statistically similar to conventional fertilization, confirming the importance of vermicomposting in production system with restricted access to industrialized products. It is concluded that vermicomposting did not increase the release of nutrients contained in the basalt powder when prepared and applied in a Italian zucchini. It is hoped that this research contributes to a better understanding of stonemeal as an alternative practice for soil fertilization.